Evaluation of Lactobacillus plantarum efficincey and zearalenone Toxicity reducing In vitro and In vivo - Al-aboudy, Noor Alhuda A.; Al-jumaili, Sami A. (Journal of Kerbala for Agricultural Sciences, 2018)
This study was carried out in the toxines Laboratory of pathological analysis-in the College Sciences as The Evlution efficiency of Lactobacillus plantarum in decrease of Zearalenone to toxicity The aim of this study was to evalute the efficiency of Lactobacillus plantarum bacterium detoxificated of zearalenone toxin.The results and diagnose showed Fusarium spp. Fungus appearance and frequency was 32% and 5.33% respectively. Also results of Fusarium spp.test on the production of zearalenone toxin Thin layer chromatography(TLC) showed 13 isolated produced to toxin out of 18 isolation in the rate 72.22% The study results showed the effectiveness of the bacteria L. plantarum in reducing the toxicity of zearalenone externally(In vitro) since disappeared shin spot poison zearalenone treatment with bacteria from plate Thin layer chromatography when exposed UV at a 360 nm wavelength . reinforced this result vital tests that took place inside the body of animals albino Rat and the transaction of zearalenone pre-treatment bacterium L. plantarum the physiological blood parameters were completely intact and showed clear variances in the physiological blood parameters in animals treated to zearalenone only. The count of red blood cells in the treatmet bacteria and toxin 6.66x106 cell/mm3 as treated in poison treatment only 4.81x106 cell/mm3 and count of white blood cells in the treatment of bacteria and poison 13.18x103 mm3 while the treatment of poison only 14.56x103 mm3 the quantity of PCV of bacteria and poison 62.76% and the treatment of poison only 42.5%